Current Practices Regarding Perioperative Management of Patients With Fracture on Antiplatelet Therapy: A Survey of Orthopedic Surgeons. (December 2015) - Pean, Christian A.; Goch, Abraham; Christiano, Anthony; Konda, Sanjit; Egol, Kenneth
Objective: There continues to be controversy over whether operative delay is necessary for patients on antiplatelet therapy, particularly for elderly patients with hip fractures. This study sought to assess current clinical practices of orthopedic surgeons regarding perioperative management of these patients. Methods: A 12-question, Web-based survey was distributed to orthopedic surgeons via e-mail. Questions regarding timing of surgery assumed patients were on antiplatelet therapy and assessed attitudes toward emergent and nonemergent orthopedic cases as well as operative delay for specific closed fracture types. Responses were compared using unpaired, 2-tailed Student t tests for continuous variables and Pearson chi-square tests with odds ratios (ORs) and 95% confidence intervals (CIs) for categorical variables. Statistical significance was defined as a P value <.05. Results: Overall 67 orthopedic surgeons responded. Fifty-two percent (n = 35) of the respondents described their practice as academic. Thirty-nine percent (n = 25) of the surgeons indicated that no delay was acceptable for urgent but nonemergent surgery, and 78% (n = 50) reported no delay for emergent surgery was acceptable. Sixty-eight percent (n = 46) of respondents felt patients on antiplatelet therapy with closed hip fractures did not require operative delay. Surgeons who opted for surgical delay in hip fractures were more likely to delay surgery in other lower extremity fracture types (OR = 16.4, 95% CI 4.48-60.61, P < .001). Sixty-four percent (n = 41) of the surgeons indicated there was no protocol in place at their institution. Conclusions: There continues to be wide variability among orthopedic surgeons with regard to management of patients with fracture on antiplatelet therapy. Over a quarter of surgeons continue to opt for surgical delay in patients with hip fracture. This survey highlights the need to formulate and better disseminate practice management guidelines for patients with fracture on antiplatelet therapy, particularly given the aging population in the United States.